2018
DOI: 10.1111/bjh.15730
|View full text |Cite
|
Sign up to set email alerts
|

The Duffy antigen receptor for chemokines, ACKR1,– ‘Jeanne DARC’ of benign neutropenia

Abstract: Summary Benign neutropenia, observed in different ethnic groups, is the most common form of neutropenia worldwide. A specific single nucleotide polymorphism, rs2814778, located at the promoter of the ACKR1 (previously termed DARC) gene, which disrupts a binding site for the GATA1 erythroid transcription factor, resulting in a ACKR1‐null phenotype, was found to serve as a predictor of low white blood cell and neutrophil counts in African‐Americans and Yemenite Jews. Individuals with benign neutropenia due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 98 publications
(171 reference statements)
0
35
1
Order By: Relevance
“…Therefore, further research with larger sample sizes in various populations is required. The Rs2814778, a specific SNP at the DARC gene promoter, results in a DARC-null phenotype and has been found to be a predictor of low counts of leukocyte and neutrophil (26,27). However, in this study, it was found that DARC polymorphism (rs12075) was not significantly associated with white blood counts in HCV positive patients and it is suggested that these two SNPs have different biological functions.…”
Section: Discussioncontrasting
confidence: 64%
“…Therefore, further research with larger sample sizes in various populations is required. The Rs2814778, a specific SNP at the DARC gene promoter, results in a DARC-null phenotype and has been found to be a predictor of low counts of leukocyte and neutrophil (26,27). However, in this study, it was found that DARC polymorphism (rs12075) was not significantly associated with white blood counts in HCV positive patients and it is suggested that these two SNPs have different biological functions.…”
Section: Discussioncontrasting
confidence: 64%
“…[4] Benign, ethnic neutropenia has a high prevalence in individuals of African descent. [36,37] Therefore, ethnic neutropenia should be considered and ruled out in individuals who present with low neutrophil counts (<2 500 cells/µL). [38]…”
Section: Hiv-associated Neutropeniamentioning
confidence: 99%
“…sickle cell, α/β-thalassemia) more common among African, Mediterranean and Asian populations (Beutler and West, 2005; Raffield et al, 2018; Rana et al, 1993). AFR individuals tend to have lower WBC and neutrophil counts partly because of the Duffy/ DARC null variant (Rappoport et al, 2019). Among Hispanics/Latinos (HA), a common Native American functional intronic variant of ACTN1 is associated with lower PLT count (Schick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%